2021
DOI: 10.1186/s12882-021-02471-2
|View full text |Cite
|
Sign up to set email alerts
|

Community- versus hospital-acquired acute kidney injury in hospitalised COVID-19 patients

Abstract: Background Acute kidney injury (AKI) is a recognised complication of coronavirus disease 2019 (COVID-19), yet the reported incidence varies widely and the associated risk factors are poorly understood. Methods Data was collected on all adult patients who returned a positive COVID-19 swab while hospitalised at a large UK teaching hospital between 1st March 2020 and 3rd June 2020. Patients were stratified into community- and hospital-acquired AKI bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
1
17
1
7
Order By: Relevance
“…Today the benefits of e-alerts are largely passive, and remains untackled by many institutions, especially those with limited resources or have no mandate to establish such a system. The benefits highlighted by national alerts systems in the UK [ 65 , 73 , 79 ] or in specific use case scenarios of nephrotoxic surveillance [ 41 , 85 , 91 ], or simply AKI surveillance [ 43 ], are valuable and provide an example of what is possible. To realize the full potential of AKI alerts, some rule modifications may be necessary in terms of how AKI is defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Today the benefits of e-alerts are largely passive, and remains untackled by many institutions, especially those with limited resources or have no mandate to establish such a system. The benefits highlighted by national alerts systems in the UK [ 65 , 73 , 79 ] or in specific use case scenarios of nephrotoxic surveillance [ 41 , 85 , 91 ], or simply AKI surveillance [ 43 ], are valuable and provide an example of what is possible. To realize the full potential of AKI alerts, some rule modifications may be necessary in terms of how AKI is defined.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the algorithm for AKI detection, a consistent nationwide alert system seems like a challenge in North America and the studies published from the UK have generally shown to be beneficial from a detection and alerting standpoint [ 43 , 65 , 73 , [79] , [80] , [81] ]. Some studies as discussed below have also reported improved clinical outcomes [ 65 , 80 , 81 ].…”
Section: Serum Creatinine (Scr) For Diagnosing Akimentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the distinction between community and hospital acquired AKI, often, a 48-hour threshold is used to identify CA-AKI [ 31 ]. Such a definition would preclude many patients in this study who were identified as having AKI on day 3 of admission.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the distinction between community and hospital acquired AKI, often a 48 hr threshold is used to identify CA-AKI [28]. Such a definition would preclude many patients in this study who were identified as having AKI on day 3 of admission.…”
Section: Discussionmentioning
confidence: 99%